Development of Mobile Learning as a Student Career Planning Media at Senior High School 1 Talang Ubi - Veronica, Nia; Purwanta, Edi; Mahardhika, Muhammad (International Journal of Applied Guidance and Counseling, 2021)
Background of this research is the lack of students' understanding of career planning, there are several career problems faced by students. This study aims to produce a mobile learning-based career planning application at Senior High School 1 Talang Ubi. This development research refers to the steps of research and development (R&D) by Borg and Gall. Subjects in the initial field trial 6 students scored 79.46 in the very good category, the main field trial 12 students scored 84.07 in the very good category, and the operational field trial 32 students scored 94.47 in the very good category.  good.  Subject selection was based on the purposive sampling technique. The results showed that (1) the media produced was in the form of a career planning application using Adobe AIR for Android Version 0.1, (2) the mobile learning produced according to experts was suitable for use as a medium for student career planning at Senior High School 1 Talang Ubi.